Juridical Study of Illegal Logging Crimes in Forest Areas in Grobogan Regency - Ahmad Dicky Muttaqin; Syifa Rana Tsary (CV. Cognispectra Publishing, 2025)
This study aims to determine and analyze why rampant illegal logging in forest areas is the main problem in Grobogan Regency. The area still has a beautiful natural atmosphere and extensive forests planted with teak trees managed by Perum Perhutani. The author is interested in researching the formulation of the problem: how are the criminal regulations for illegal logging in forest areas, and how are forest protection efforts due to illegal logging? This research method uses a type of sociological normative research which is carried out by searching for secondary data in the form of primary legal materials, namely legal document inventories; secondary legal materials, namely books, journals or other literature; and tertiary legal materials, as well as conducting interviews in the field with perpetrators of illegal logging in Grobogan Regency. The results of this study indicate that the crime of illegal logging is regulated in the Criminal Code (KUHP) and Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction. As for forest protection efforts, there are several ways to overcome the impacts resulting from logging.